Identification algorithms of flexible structure using neural networks - Ismail, Razali; Ismail, A.Y; Mat Darus, I.Z. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org